Penilaian Kepuasan Karyawan pada Sistem Pengelolaan Organisasi di RSUD Dr. Soetomo Surabaya - Maya Weka Santi; Thinni Nurul Rochmah (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2018)
Background: Assessment of employee’s job satisfaction in an organization management system was conducted periodically by Dr. Soetemo Hospital. The data can be an archive of organizational value, supervision reinforcement, and effective communication for the manager. The measurement of employees’ job satisfactionwas performed through Job Description Index (JDI).Aim: The aim of the research was to measure job satisfaction level of the employee at Dr. Soetomo Hospital.Method: The population of this study was 4347 employees at Dr. Soetomo Hospital, but only 413 were taken as the samples. The sample was calculated by Slovin formula. This sample size was taken based on proportional number of profession and department at Dr. Soetomo Hospital.Results: Most of the employees gave good assessment on Job Description Index (JDI) indicators among others which include job in general (78.9%), pay (59.1%), opportunities for promotion (67.3%), supervision (74.6%), people in present job (73.6%) and work in Present Job (72.9%). If JDI indicators are valued as employees’ job satisfaction, it can be said that most of employees felt satisfied about the organization’s management system at Dr. Soetomo Hospital, Surabaya (80,6%). However, there were still 12.3% of employees feeling unsatisfied about the organization’s management system at Dr. Soetomo Surabaya Hospital.Conclusion: Overall, many staffs mentioned that their income and compensation were respectively bad and very bad. The study provides implications for increasing opportunities of staff’s salary and career path such as promotions.Keywords: employee’s job satisfaction, hospital, Job Description Index